Inflation and Fair Market Value: An Empirical Analysis of Sales Transactions of U.S. Closely-Held Companies - Merrill, Gregory B.; Galbraith, Craig S.; Stiles, Curt H. (JABM, 2011)
In this paper we examine the relationship between inflation regimes, inflation volatility and the valuation of closely-held firms. Using sales transaction data we found that the relationship between valuation and inflation for closely-held firms appears similar to that found in prior research from publicly traded firms. Using four different measures of valuation, there appears to be a bimodal relationship where very low inflation and very high inflation is associated with lower valuations, while a sweet spot' between two percent and four percent inflation is associated with the highest valuations. Valuations also appear negatively correlated with inflation volatility.